Bus Rapid Transit-oriented Development: An Identification of Bus Rapid Transit System Passengers’ Modal Shift Potential Considerations - Prayogi, Lutfi; Satwikasari, Anggana Fitri (UI Scholars Hub, 2019)
This article explores some issues that are potentially considered by bus rapid transit (BRT) system passengers when shifting their mode of transport from driving their personal vehicle to taking the BRT system for the same kind of trip. The issues are explored as part of an attempt to design an appropriate BRT passengers’ modal shift evaluation. The BRT passengers’ modal shift evaluation is to be carried out to understand how a BRT system may influence urban development around the system and how it may trigger transit-oriented development (TOD) around the system. This article was written through a literature review directed on certain topics, that are BRT ridership-influencing factors, the BRT system passengers’ behaviour, the built environment condition around BRT systems, the types of transit system passengers and the types of trips carried out utilising a transit system. It is found that several components of BRT system service quality and several components of built environment around the system potentially influence the BRT system passengers’ consideration when shifting their mode of transport. However, the influence may not be homogenous among all passenger-trips due to the different passengers’ backgrounds and the different types of trips carried out utilising the BRT system.